Longitudinal profile of circulating T follicular helper lymphocytes parallels anti‐HLA sensitization in renal transplant recipients. Issue 1 (25th July 2018) - Cano‐Romero, Francisco Luis; Laguna Goya, Rocío; Utrero‐Rico, Alberto; Gómez‐Massa, Elena; Arroyo‐Sánchez, Daniel; Suárez‐Fernández, Patricia; Lora, David; Andrés, Amado; Castro‐Panete, Mª José; Paz‐Artal, Estela
Abstract : Antibody‐mediated rejection is responsible for 30%‐50% of renal graft failures. Differentiation of B cells into antibody‐producing plasmablasts depends on the collaboration of follicular helper T cells (Tfh). We analyzed circulating Tfh (cTfh) in kidney recipients and studied cTfh relationship with anti‐HLA antibody production and graft outcome. cTfh were longitudinally analyzed in a prospective cohort of patients (n = 206), pre‐ and posttransplantation. Clinical data, HLA sensitization, and cTfh function were recorded. Both pretransplant and 6‐month posttransplant cTfh were able to derive IgG‐producing plasmablasts. Pretransplant cTfh was decreased in patients, especially in those who received dialysis. However, these cells were increased in patients with previous allograft or transfusions and in HLA‐sensitized recipients. After transplantation cTfh expanded, significantly more in patients who developed de novo anti‐HLA antibodies than in patients who remained unsensitized. Augmented pretransplant cTfh positively correlated with higher intensity of pretransplant anti‐HLA class I and with de novo anti‐HLA class I and anti‐HLA class II antibodies. Consistently, pretransplantation cTfh were higher in patients who experienced acute rejection (HR = 1.14 [1.04‐1.25]). Thus, we show a role for Tfh in anti‐HLA sensitization and rejection. Multicenter studies with additional patient cohorts are needed to validate these results. Immunosuppressive drugs targeting Tfh could be useful to improve outcomes. Abstract : Circulating follicular helper T cells are associated with anti‐HLA antibody development and acute rejection in renal transplant patients, which points these cells out as a therapeutic target to improve transplant outcome.